Necessity-Driven Entrepreneurship, Job Creation, and Structural Unemployment: Cross-Country Panel Evidence with Qualitative Insights - Hery Margono (Yayasan Sinergi Kawula Muda, 2026)
This study examines the association between necessity-driven entrepreneurship (NDE), job creation, and structural unemployment using a convergent mixed-methods design. The quantitative strand uses cross-country panel data from 45 countries over 2013–2023, drawing on GEM, World Bank, ILO, and governance datasets. Two-way fixed-effects models with Driscoll–Kraay standard errors are complemented by system GMM robustness checks and bootstrap-based mediation tests. The qualitative strand draws on 12 semi-structured interviews with necessity entrepreneurs, policy officials, entrepreneurship program administrators, and labor market experts to contextualize the quantitative patterns. The findings indicate that higher NDE is associated with lower structural unemployment and higher formal employer entry, with evidence consistent with a partial formal job-creation pathway linking NDE and structural unemployment. The results further suggest that institutional support and human capital condition the strength of these associations. Interview evidence illustrates plausible mechanisms, including regulatory friction, financing constraints, formalization barriers, and managerial capability gaps. Because the study relies on observational cross-country data and formal-sector proxies, the findings should be interpreted as evidence of conditional associations rather than definitive causal effects. The study contributes by clarifying the circumstances under which NDE may function as a productive labor market adjustment mechanism.